2018
DOI: 10.1016/j.addma.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compatibility of fused filament fabrication-based 3-D printed components with solutions commonly used in semiconductor wet processing

Abstract: 3-D printing shows great potential in laboratories for making customized labware and reaction vessels. In addition, affordable fused filament fabrication (FFF)-based 3-D printing has successfully produced high-quality and affordable scientific equipment, focusing on tools without strict chemical compatibility limitations. As the additives and colorants used in 3-D printing filaments are proprietary, their compatibility with common chemicals is unknown, which has prevented their widespread use in laboratory che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
5
32
0
Order By: Relevance
“…Other studies that revealed PP's potential as an engineering material with excellent stability against chemicals include the production of chemical process laboratories or chemical reaction vessels, for example, for the synthesis of bicyclic and tetracyclic heterocycles, the anti‐inflammatory drug ibuprofen, or multistep organic syntheses, the production of microfluidic devices for the medical and chemical industry, the fabrication of tailored reactor devices for mass spectrometry, or reactionware devices for continuous‐flow organic reactions . Additionally, various researchers recommended the use of 3D‐printed PP for various promising applications, such as for a chemically resistant laboratory equipment for the processing of semiconductors, for terahertz devices, or for a cheap and light weight alternative for the electrolysis of water …”
Section: Potential Applications For 3d‐printed Ppmentioning
confidence: 99%
“…Other studies that revealed PP's potential as an engineering material with excellent stability against chemicals include the production of chemical process laboratories or chemical reaction vessels, for example, for the synthesis of bicyclic and tetracyclic heterocycles, the anti‐inflammatory drug ibuprofen, or multistep organic syntheses, the production of microfluidic devices for the medical and chemical industry, the fabrication of tailored reactor devices for mass spectrometry, or reactionware devices for continuous‐flow organic reactions . Additionally, various researchers recommended the use of 3D‐printed PP for various promising applications, such as for a chemically resistant laboratory equipment for the processing of semiconductors, for terahertz devices, or for a cheap and light weight alternative for the electrolysis of water …”
Section: Potential Applications For 3d‐printed Ppmentioning
confidence: 99%
“…The mechanical properties of FFF/FDM PLA are well established [20][21][22][23], and their chemical resistance is also known [24]. PLA has also been successfully used in a number of polymer matrix composites [25][26][27][28][29][30]. These advances in sandwich structures and polymer/natural fibre composites open up the potential to overcome one of the primary limitations of FFF/FDM in load bearing applications: highly anisotropic properties having particularly low stiffens and strength in the direction of layer deposition (z-direction) [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Although the most common thermoplastics used are PLA and ABS, alternative thermoplastics can be also furnished to take advantage of different material properties. [28] Carbon nanotubes/graphene/ polybutylene terephthalate, carbon nanofiber/graphite/polystyrene composite or carbon fiber/PLA are some additional examples of filaments employed to achieve electrically conductive printable composite electrodes. [29,30] Inks: The most common conducting inks used for electrochemical sensing devices manufacturing are based on metal nanoparticles, metallo-organic decomposition (MOD) and inorganic salts.…”
Section: Methodsmentioning
confidence: 99%